Characterization of gut microbiota and metabolites in individuals with constipation-predominant irritable bowel syndrome - Wang, Ya-Li; Xu, Xiao-Qian; Long, Yi-Yan; Cheng, Yan-Li (Frontiers in Microbiology, 2025)
ObjectiveConstipation-predominant irritable bowel syndrome (IBS-C) is a prevalent functional gastrointestinal disorder with an incompletely understood pathogenesis. Recent studies have found that gut microbiota may contribute to its development. This study aimed to characterize the gut microbiota and associated metabolites in individuals with IBS-C to investigate potential pathogenic mechanisms.MethodsA total of 22 individuals diagnosed with IBS-C and 22 healthy controls were recruited at the First Hospital of Tsinghua University between January and December 2023. Stool samples were collected and subjected to metagenomic and metabolomic analyses to assess microbial composition and metabolic profiles. Bioinformatic analyses were employed to integrate and interpret the data.ResultsMetagenomic sequencing results indicated no significant differences in overall gut microbial diversity between the IBS-C group and healthy individuals (p > 0.05). However, six bacterial species exhibited differential abundance. Notably, the relative abundance of beneficial taxa such as Megasphaera elsdenii, Bifidobacterium bifidum, and Alistipes inops was significantly reduced in the IBS-C group (p < 0.05). Metabolomic profiling demonstrated that differential metabolites were primarily enriched in pathways related to 3 short-chain fatty acids (SCFA) metabolism. SCFA levels were significantly downregulated in individuals with IBS-C, and a trend toward increased levels of the pro-inflammatory metabolite leukotriene D5 was observed.ConclusionIndividuals with IBS-C demonstrate gut microbiota dysbiosis, characterized by reduced abundance of specific probiotic species and altered SCFA metabolism, along with potential low-grade inflammatory activity. These findings offer insights into the pathophysiological mechanisms of IBS-C and may inform the development of new therapeutic strategies.